Humanitarian Action of United Nations International Children’s Emergency Fund (UNICEF) in Jayapura During the Covid-19 Pandemic - Claudia Conchita Renyoet; Made Selly Dwi Suryanti; M Zaenul Muttaqin (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2023)
The issue of humanitarianism in international relations is a vital topic to probe deeper. Activist groups, individuals, and institutionalized groups or organizations, such as the United Nations International Children's Emergency Fund (UNICEF), have been carrying out humanitarian actions in Papua. UNICEF has been around for a long time in Papua, running several programs, including children's education program in Papua. However, education in Papua remains relatively low due to high rates of illiteracy and school dropouts, and poor literacy. This research explains that international organizations working in the humanitarian field can carry out the basic principles of humanitarianism, specifically, how UNICEF's programs adhere to these principles during the Covid-19 era. Direct interviews and secondary data collection were conducted in this qualitative descriptive research. The results show that UNICEF, as an international humanitarian organization, managed to uphold four basic principles in carrying out its role, particularly in improving the quality of education in Jayapura City. However, the Covid-19 pandemic has posed such obstacles to UNICEF related to donors, program implementation, and personnel that the practiced humanitarian principles became blurred and somewhat questionable. While the best practice promotes faithful adherence to the basic principles of humanity, it is undeniable that almost all organizations cannot exist without assistance from third parties which would ignore the principle of impartiality. Keywords: Covid-19, education, humanitarianism, Jayapura, UNICEF